Utilization of Multimedia in the Process of Learning in Elementary School - Bakkidu, Nurhinda; Sumartini, Sumartini (Universitas Negeri Makassar, 2014)
The purpose of research of this is to examine the use of multimedia in the learning process. This research subject is pupils and teacher in Inpres Perumnas II elementary school, Makassar. Data obtained through observation, interviews and dokumentasi.Data analyzed by descriptive statistical analysis techniques. The analysis showed (1) the overall teachers understand the benefits of multimedia, (2) teachers already use multi media, (3) the teacher often combines original media and visual media, (4) is still less provided the media at the school, (5) teachers in utilizing multimedia in the learning process begins with preparing lesson plans, (6) some teachers have problems in terms of lack of inability to use the media systematically based on varied purposes, and (7) the efforts of teachers in overcoming barriers they experienced is by setting up its own media.